Consideraciones metodológicas acerca de los sondeos de opinión (2009)
ABSTRACT: The researchers often try to measure the public opinion through the opinion polls. There are problems keys to consider: the design sample, the design of the questions of the questionnaire and the attempts to generalize the results from a study to a population that does not reunite the characteristics of the sample."